A study of the structure and iconography of tamgas in the “Dongoin Shiree” monument (Studia Archaeologica, 2026)
Among the diverse manifestations of Mongolia’s stone heritage are tamga engravings found on both natural rock surfaces and intentionally shaped stone monuments. These tamga inscriptions occur either independently or in conjunction with petroglyphs and written scripts. Such monuments belong to different chronological periods and preserve invaluable information regarding the clan and tribal systems, sociopolitical organization, territorial demarcation, linguistic and cultural development, ethnic identity, and symbolic beliefs of the respective eras. The “Dongoin Shiree” complex, located within the territory of Tüvshinshiree soum, Sükhbaatar province, represents one such significant site that contains an assemblage of stone monuments bearing engraved tamgas. The variety, composition, proportional relationships, and semantic content of these tamgas constitute important material for historical and archaeological inquiry. This article aims to conduct a detailed analysis of the tamga motifs found at the “Dongoin Shiree” monument, focusing on their placement, proportions, forms, meanings, and compositional characteristics. Furthermore, it seeks to interpret these features from archaeological, historical-comparative, and iconographic perspectives. By comparatively examining the traditions, meanings, and symbolism of ancient tamga signs, the study also aims to identify their cultural characteristics and semantic functions.“Донгойн Ширээ”-ний дурсгал дахь тамганы бүтэц ба дүрслэлийн судалгаа Хураангуй: Монгол орны нутаг дэвсгэр дэх чулуун өв соёлын нэг нь байгалийн хад чулуу болон зориуд засаж бэлдсэн хөшөө чулуунд сийлж үлдээсэн тамга тэмдгийн дурсгал юм. Тамга тэмдгийн дурсгал нь дангаар байхаас гадна элдэв сүг зураг болон бичиг үсгийн хамт дүрслэгдсэн байх нь олонтоо ажээ. Энэ төрлийн дурсгалууд нь харилцан адилгүй он цагт хамаарах бөгөөд тухайн үеийн овог аймаг, нийгмийн бүтэц зохион байгуулалт, газар нутаг, хэл соёл, угсаатан хийгээд бэлгэдэл зүйн талаарх үнэт мэдээллийг хадгалсан байдаг. Ийм дурсгалын нэг бол Сүхбаатар аймгийн Түвшинширээ сумын нутаг “Донгойн Ширээ” хэмээх газраас илэрсэн олон хөшөөт цогцолбор дурсгал дахь тамганы дүрслэл юм. Энэ дурсгалын хөшөө чулуунд сийлсэн тамга, түүний төрөл, дүрслэл, хоорондын харьцаа болон агуулга зэрэг нь судалгааны чухал ач холбогдолтой хэсэг юм. Тус өгүүлэлд “Донгойн Ширээ”-ний дурсгал дахь тамганы дүрс, тэдгээрийн байрлал, харьцаа, хэлбэр болон агуулга, зохиомжийн онцлогийг нарийвчлан шинжилж, археологийн болон түүхэн-харьцуулалт, дүрслэл зүйн үүднээс тайлбарлахыг зорьсон болно. Мөн эртний тамга тэмдгийн уламжлал, утга агуулга, бэлгэдлийг харьцуулан үзэх замаар соёлын онцлог, утга зүйн үүргийг тодорхойлохыг зорив.Түлхүүр үг: хөшөө чулуу, дүрс, сийлмэл, овог аймаг, тамга, янгир, онги